2007
DOI: 10.1205/psep07009
|View full text |Cite
|
Sign up to set email alerts
|

Cold Flow Properties of Fatty Esters

Abstract: SummaryTh e article is devoted to the study of cold fl ow properties of neat esters of branched chain alcohols with fatty acids and blends of these esters with fossil diesel fuel. According to the determined CFPP values the infl uence of alcohol branching on the fuel fi lterability is negligible and was detected only in the case of 2-ethyl hexanol. Fossil fuel blending with fatty esters up to 10 % vol. does not substantially change the cold fl ow properties of fossil fuel. DSC cooling scan parameters should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 11 publications
3
17
0
Order By: Relevance
“…For example, biodiesel derived from PME has a cloud point that ranges from 10 C to 20 C, which may cause trouble in cold seasons. Kleinová et al 154 used palm oil based biodiesel and conrmed that the cold ow behavior of FAME/FAEE is one of 34 reported that diesel engine start ability can be deteriorated at under-zero ambient temperature, which also creates problems of fuel starvation and operability when solidied materials clog fuel lines and lters due to the crystallization of saturated FAME components. When ambient temperature decreases, additional solids are created.…”
Section: Asean Basedmentioning
confidence: 99%
“…For example, biodiesel derived from PME has a cloud point that ranges from 10 C to 20 C, which may cause trouble in cold seasons. Kleinová et al 154 used palm oil based biodiesel and conrmed that the cold ow behavior of FAME/FAEE is one of 34 reported that diesel engine start ability can be deteriorated at under-zero ambient temperature, which also creates problems of fuel starvation and operability when solidied materials clog fuel lines and lters due to the crystallization of saturated FAME components. When ambient temperature decreases, additional solids are created.…”
Section: Asean Basedmentioning
confidence: 99%
“…There are different commercial additives for diesel and their blends with biodiesel, but for the additives to become effective, a much higher concentration is needed than the one used in this work . However, this paper presents PP reductions for palm oil methyl esters and their blends significantly better than those found in the literature …”
Section: Resultsmentioning
confidence: 65%
“…However, different plant oils produce biodiesel with different chemical compositions; and thus, blends of various oils are required to produce desirable products. The process of transesterification produces monoglycerides (usually glycerine) as a by-product which largely functions as a feedstock for cosmetics (AMEC 2007;Kleinová et al, 2007). The production of bioethanol is carried out through some edible plant material such as sugarcane, sugar beet and corn kernels, since they can be easily decomposed to glucose which further can be fermented to ethanol through the microbes like yeasts (e.g.…”
Section: Biofuelsmentioning
confidence: 99%